Applying the comprehensive model of information seeking to understand chronic illness information scanning: Hong Kong evidence. Issue 2 (21st April 2022) - Fung, Timothy K. F.; Lai, Po Yan; Chang, Leanne; Leung, Ho Man
Abstract: Chronic illness is the most prevalent and costly global public health challenge. To address this challenge, health information is essential for individuals to make informed decisions to self‐manage their health and prevent and monitor chronic illness. Although previous studies show that health information scanning—a form of information gathering behavior to obtain health information, incidentally, when health topics of interest arise during daily conversations with others or through regular use of the media—positively influenced health decisions, little is known about information scanning in the context of chronic illness. This study applied the Comprehensive Model of Information Seeking to examine factors that influence individuals' use of different channels for health information scanning. Using quota sampling to resemble population demographic characteristics, we collected 1100 online survey responses from Chinese‐speaking Hong Kong residents aged from 18 to 65 or older. Three structural equation modeling analyses were performed to examine how antecedent factors and information carrier factors influenced the use of interpersonal/group channels, the Internet‐related channels, and the traditional media channels for scanning chronic illness‐related information. The findings supported that channel utility was an important determinant of health scanning behavior, and channel characteristics were strong predictors of channel utility. However, mixed findings were observed on the relationship between antecedent factors and channel utility across the three‐channel categories, because some antecedent factors had direct influence on health information scanning. These findings will inform the information dissemination and promotional message design for chronic illness prevention and care. Key points: Consistent with predictions of the comprehensive model of information seeking, the more individuals perceive that messages carried by an information channel are personally relevant and useful to them, the more likely they will scan health information using that channel. Furthermore, the more individuals perceive the message content to contain positive characteristics, the more likely they perceive the messages carried by the channels as relevant and useful to them. Of antecedent factors, belief‐related variables (perceived benefits and drawbacks of regular physical checkups, and efficacy belief) showed significant influences on people's perception of information channel utility and their health information scanning behavior. When designing promotional messages and disseminating information related to chronic illness care and prevention, it is important to consider factors of perceived benefits and drawbacks of regular physical checkups, efficacy belief, age, worry, and insurance/subsidy.